1,5 – 2 gadīgu bērnu runas aktivizēšana pedagoģiskajā procesā pirmsskolā - Roķe, Laima (Latvijas Universitāte, 2020)
Kvalifikācijas darba temats:” 1,5-2 gadīgu bērnu runas aktivizēšana pedagoģiskajā procesā pirmsskolā”. Mērķis: izzināt 1,5-2 gadīgu bērnu runas attīstības sekmēšanas iespējas pedagoģiskajā procesā. Darba pirmajā daļā tiek iepazīstināts ar runas un valodas jēdzienu, funkcijām un to dažādajām izpausmēm. Vērsta uzmanība uz 1,5 – 2 gadīgu bērnu runu, tās attīstību un faktoriem, kas to ietekmē. Darba empīriskajā daļā tika pētīts, kā ar rotaļu palīdzību var veicināt, aktivizēt 1,5-2 gadīgu bērnu runas attīstību dažādās rotaļās, (pirkstu rotaļās, kustību rotaļās un rotaļās ar dziedāšanu); un praktisku darbošanos. Pētījuma sākumā tika veikts bērnu runas attīstības novērojums. Pētījuma laikā tika organizētas dažādas rotaļas, kas sekmē bērnu runas attīstību. Pētījuma beigās tika veikts atkārtots bērnu runas attīstības līmeņa raksturojums. Darbs sastāv no divām daļām, tā apjoms ir 54 lpp. Tajā iekļautas 3 tabulas, 8 pielikumi un 9 attēli. Darbam tika izmantotas 44 bibliogrāfiskās satura vienības Atslēgvārdi: runa, valoda, pedagoģiskais process pirmsskolā, rotaļa, spēle

The topic of the qualification work: '' 1.5-2 years old children 's speech activation in the pedagogical process in preschool'. The Aim: to find out the possibilities of 1.5-2 years old children to promote speech development in the pedagogical process. The first part of the work with speech and language concepts, functions and some manifestations of needs. Focuses on the speech of 1.5 -2 year old children, its development and the factors that affect it. In this chapter, the author describes the general concept and essence of language and speech, as well as the importance of language in a child's development. The second part of the work, it was investigated how play can be used to improve, activate the race of 1.5-2 year old children, which changed in different games (finger games, movement games and games with singing); and practical operation. The third part of the work - was studied, how through games it is possible to activate, activate the race of 1.5–2-year-old children, which developed in various games (finger games, movement games and games with singing); and practical operation. At the beginning of the study, observations of children's speech development were used. Various games were played during the study. At the end of the study, a repeated level of children's speech development was applied. At the end of the study, the level of children's speech development was repeated. The work consists of two parts, its volume is 54 pages. It includes 3 tables, 8 appendices and 9 figures. 44 bibliographic content units were used for the work Sent: speech, language, pedagogical process in preschool, play, game
Activation of speech of 1.5 - 2 year old children in the pre-school pedagogical process
Keywords: Pirmsskolas pedagoģija; runa; valoda; pedagoģiskais process pirmsskolā; rotaļa; spēle